The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/ph12040144
|View full text |Cite
|
Sign up to set email alerts
|

What Is Next in This “Age” of Heme-Driven Pathology and Protection by Hemopexin? An Update and Links with Iron

Abstract: This review provides a synopsis of the published literature over the past two years on the heme-binding protein hemopexin (HPX), with some background information on the biochemistry of the HPX system. One focus is on the mechanisms of heme-driven pathology in the context of heme and iron homeostasis in human health and disease. The heme-binding protein hemopexin is a multi-functional protectant against hemoglobin (Hb)-derived heme toxicity as well as mitigating heme-mediated effects on immune cells, endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 138 publications
0
16
0
Order By: Relevance
“…In summary, we re-evaluate the heme-hemopexin interaction and propose a new K D value together with a heme-recruiting mechanism. These novel insights may contribute valuable information regarding hemopexin’s function and applicability that are currently under investigation in other laboratories, such as its antithrombotic and antiinflammatory effect 20,43,47 . While hemopexin is currently being considered for the treatment of intracerebral hemorrhage (ICH) 48 , it might also be administered for the therapy of heme overload conditions, such as in sickle cell disease or β-thalassemia 47,49,50 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In summary, we re-evaluate the heme-hemopexin interaction and propose a new K D value together with a heme-recruiting mechanism. These novel insights may contribute valuable information regarding hemopexin’s function and applicability that are currently under investigation in other laboratories, such as its antithrombotic and antiinflammatory effect 20,43,47 . While hemopexin is currently being considered for the treatment of intracerebral hemorrhage (ICH) 48 , it might also be administered for the therapy of heme overload conditions, such as in sickle cell disease or β-thalassemia 47,49,50 .…”
Section: Discussionmentioning
confidence: 97%
“…Hemopexin plays a major role in humans by detoxifying heme and preventing organismal damage under hemolytic conditions 5 . Several reports show its applicability as therapeutic agent 5,19,20,42,43 . This advancement in the medical application of hemopexin stands in strong contrast to the knowledge available regarding the exact nature of the heme-hemopexin interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemopexin (HPX) is a glycoprotein in plasma which binds to free heme and; therefore, plays an important role in detoxifying heme and lipid oxidation [ 44 ]. Plasma HPX level is; therefore, an important biomarker for inflammatory and oxidative stress [ 45 , 46 ]. Our results showed that dietary PO increased plasma HPX levels.…”
Section: Discussionmentioning
confidence: 99%
“…While this review summarized the data on Tfr2 extrahepatic role, including the importance of the two main isoforms, Tfr2α and Tfr2β, the use of Tfr2 as therapeutic target for hepcidin control is also discussed. Finally, the systemic iron regulation, achieved by controlling heme metabolism, was described by Montecinos et al [25], who reviewed the present knowledge on the heme-binding protein hemopexin (HPX) and provided information on its biochemistry. HPX prevents the toxicity induced by hemoglobin (Hb)-derived heme, which occurs in hemolytic conditions and can be triggered by the activation of the immune system.…”
mentioning
confidence: 99%